Rhodium(iii)-catalysed cascade [3 + 2] annulation of N-aryloxyacetamides with 3-(hetero)arylpropiolic acids: synthesis of benzofuran-2(3H)-ones. Issue 37 (13th September 2019) - Pan, Jin-Long; Liu, Tuan-Qing; Chen, Chao; Li, Quan-Zhe; Jiang, Wei; Ding, Tong-Mei; Yan, Zhi-Qiang; Zhu, Guo-Dong
Abstract : We first reported the rhodium(iii )-catalyzed cascade [3 + 2] annulation of N -aryloxyacetamides with propiolic acids affording benzofuran-2(3 H )-ones. Abstract : Herein, a cascade [3 + 2] annulation of N -aryloxyacetamides with 3-(hetero)arylpropiolic acids affording benzofuran-2(3 H )-ones via rhodium(iii )-catalyzed redox-neutral C–H functionalization/isomerization/lactonization using an internal oxidative directing group O–NHAc was achieved. This catalytic system provides a regio- and stereoselective approach to synthesize ( Z )-3-(amino(aryl)methylene)benzofuran-2(3 H )-ones with exclusive Z configuration selectivity, acceptable yields and good functional group tolerance. Preliminary investigations on ultraviolet–visible and fluorescence behaviors reveal that the annulation products may be applied as a promising fluorescent probe for sensing metal cations, especially for cerium (Ce 3+ ).